METODE PENDIDIKAN KETELADANAN DALAM KITAB TARBIYATUL AULAD FIL ISLAM KARYA ABDULLAH NASHIH ULWAN - Ellis Eriska (Tarbiya Islamica, 2015)
This research is based on the importance of exemplary education efforts from parents and teachers to children who refer to the example of the Rasulullah SAW. In order for education to run in accordance with Islmaic Religious principle, parent and teacher need to understand and pay attention to the main components in education, one of which is the educational method of many references that discuss exemplary education method according to Islamic teaching, the book Tarbiyatul Aulad Fil Islam by Abdullah Nashih Ulwan is an interesting eading source to study, because its containsmany lessons, so it can be a reference for parent and teachers in providing exemplary education to children by referring to the example of the propet Muhammad. The purpose of this research is to describe and analyze 1) the example of Rasulullah SAW in worship based on the book of Tarbiyatul Aulad Fil Islam, 2) The example of Rasulullah SAW in morals based on the book Tarbiyatul Aulad Fil Islam, 3) The value of exemplary education in the book of Tarbiyatul Aulad Fil Islam. This research uses a qualitative approach that is library research, with the type of text or document study. The data collection technique uses document analysis, while the data analysis technique uses content analysis. The results of this study indicate that, The example of Rasulullah SAW in worship based on the book Tarbiyatul Aulad Fil Islam by Abdullah Nashih Ulwan is a) prayer, b) fasting, c) prayer beads. The example of the prophet SAW in morals based on the book Tarbiyatul Aulad Fil Islam by Abdullah Nashih Ulwan is, a) generous nature or likes to give, b) zuhud, c) tawadhu or humality, d) forgiving and generous, e) physical strength, f) brave, g) firmness in upholding the principles. The exemplary educational values of the prophet Muhammad SAW based of the book Tarbiyatul Aulad Fil Islam by Abdullah Nashih Ulwan are, a) the guidance of the Prophet Muhammad SAW in honesty, b) guidance of the prophet Muhammad SAW in justice, c) guidance of the prophet Muhammad SAW in love, d) the guidance of the prophet Muhammad SAW in filial piety to booth parents, e) guidance of the prophet Muhammad in a gentle nature.